Diplomasi Pariwisata Halal Nusa Tenggara Barat - Alfawi Ridho Subarkah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2018)
This article discusses the growing trend of halal tourism in the world, including in Indonesia. By using qualitative method and conceptions of public diplomacy and nation branding, the results of this study show a model of halal tourism applied in West Nusa Tenggara. In this model, there are two indicators: halal certification requirements for tourism products and services as well as emphasizement of community involvement as the main actors of public diplomacy. In its development, this effort managed to attract tourist visits each year, also attract foreign investors to invest in halal tourism. Through the review of the model and its accomplishment, it can be stated that halal tourism is a new form of Indonesia’s public diplomacy.